Effects of multisensory method and cogntitive skills training on perpetual performance and reading ability among dyslexic students in Tehran, Iran - Nourbakhsh, Seyed Morteza (2014)
Dyslexia is an unusual type of severe reading disability that has puzzled the educational and medical communities for many years. Dyslexic affects four percent of the population in United States of American. However some studies on dyslexia in Iran indicate the incidence of dyslexia in all grades generally was about 10%. The most important factor in dyslexia is reading downfall. The purpose of this research was to examine the effects of cognitive and developmental interventions on perceptual performance and reading ability of male dyslexic students in Iran. The investigation of perception has been a controversial issue because perception occurs within the mind and is not easy to observe, test, or measure. Cognitive skills intervention and multisensory skills intervention have been used to identify dyslexia and applied in its interventions. Also there has always been the controversial issue regarding the efficacy of the current instruments to assess perceptual abilities of dyslexic students. Therefore a major gap was filled in this research to examine the efficiency of multisensory and cognitive skills interventions in improving perceptual performance and reading ability among dyslexic students. The critical issue in randomized pre-test/post-test with control group design implied whether there were differences between the influences of interventions (multisensory and cognitive skills) on perceptual performance and reading ability of dyslexic students. It was also to determine the effective intervention for improving perceptual performance and reading ability in dyslexia. Basically, this study involves 60 dyslexic students. The respondents were divided into three experimental groups including, i.e. 20 dyslexic students as first experimental group (E1), 20 dyslexic students as second experimental group (E2), and 20 dyslexic students as control group (C). The effectiveness of the 16 weeks and 16 sessions for both E1 and E2 groups’ interventions was measured using Reading and Dyslexia Test (RDT) for distinguishing dyslexic students at the beginning and then Bender Visual Motor Gestalt Test (BVMGT) and Rorschach as non-learning based test. The results were analyzed by one-way ANOVA and paired t-test. Findings at pre-test to post-test among the three dyslexic groups demonstrated that although two groups improved from pre-test to post-test; the E1 group who followed by developmental intervention significantly improved by getting better perceptual performances in the direction of RDT, BVMGT, and R subscale of Rorschach test and indicated no significant differences in W%, D%, Dd%; however, E2 group who followed the cognitive intervention revealed significant difference in RDT, BVMGT, and R subscales of Rorschach test with no significant difference in W%, D%, and Dd% subscales of Rorschach test. From the results, it could be argued that the interventions improved subjects’ perceptual-motor performance more than their perceptual ability; however the differences occurred by the tests which are related to learning. This showed that the current perceptual tests which have been attempted to appraise the abilities originated from learning aspects would not actually be able to evaluate perceptual ability of children with dyslexia. The research findings are more consistent with developmental lag theory, which emphasizes neuro- developmental delays, and is the major cause of dyslexia. Dyslexia occurs when the students are pushed into performing academic tasks before they are able to do so. Dyslexia is not so different from other children and they need more time to learn as well as other students. The results of this research offer suggestions to consider alternatives for evaluation and remediation of these children.